Lightening of the city as a subject of geographical research (case study of Koper) - Drozg, Vladimir (Journal for Geography, 2011)
The paper deals with the illumination of the city and the geographical interpretation of this occurrence. The lit-at-night aspect of a city plays an important role in creating its image. A geographical interpretation of the city illumination thus focuses on three issues: why to illuminate, how to illuminate and who illuminates. This paper offers a discussion about the light and illumination of the city of Koper.